PENINGKATAN MUTU KAYU SAWIT DENGAN PERLAKUAN PERENDAMAN BAHAN ANTIOKSIDAN - Fakhri - (Universitas Pasir Pengaraian, 2010)
Improving the quality of palm tree trunk has been made to decreasing of fungi intensity. The research objective was to prevent the fungi at various concentrations of antioxidant substances. Antioxidant material used in the form Sodium Hipokrolit, Chlorine and Copper Sulfate each with a variation of solution concentration 5%, 10% and 15% of the weight ratio of water, soaking conducted for 24 hours, fungal growth on observations made during a week of palm wood. Results showed that soaking the material with all concentrations of Sodium Hipokrolit given still not able to prevent mildew, even should the increasing growth of fungi. Soaking with a material optimal chlorine concentration achieved at 15%. Soaking with Copper Sulfate materials can prevent of fungi at 5% concentration.